Effects of acupuncture at acupoints with lower versus higher pain threshold for knee osteoarthritis: a multicenter randomized controlled trial - Jiali Liu; Ying Li; Ling Li; Xiaochao Luo; Ning Li; Xuguang Yang; Hongxing Zhang; Zhibin Liu; Deying Kang; Yanan Luo; Yanmei Liu; Yulong Jia; et al. (BMC, 2022)
Abstract Background The acupoint selections impact the effects of acupuncture, and preliminary evidence showed potential connection between pain threshold (PT) and acupuncture response. This study examined whether acupuncture at acupoints with lower PT versus higher PT would yield different effects in patients with knee osteoarthritis (KOA). Methods In this multicenter randomized clinical trial, patients were randomly assigned (1:1:1) to receive acupuncture at acupoints with lower PT (LPT group), acupuncture at acupoints with higher PT (HPT group), and no acupuncture (waiting-list group). PT was measured with electronic von Frey detector. The primary outcome was the change in WOMAC total score from baseline to 16 weeks, and the secondary outcomes were SF-12 score, and active knee range of motion (ROM). Intention-to-treat analysis was conducted with linear mixed-effect model. Results Among 666 randomized patients, 625 (93.84%) completed the study. From baseline to 16 weeks, patients in the LPT group versus HPT group had similar effects in reducing WOMAC total score (adjusted mean difference (MD) 2.21, 95% confidence interval (CI) −2.51 to 6.92, P = 0.36), while a greater reduction in WOMAC total score was observed in LPT group (−9.77, 95% CI −14.47 to −5.07, P < 0.001) and HPT group (−11.97, 95% CI −16.71 to −7.24, P < 0.001) compared with waiting-list group. There were no differences in SF-12 score and knee ROM between LPT versus HPT groups. Conclusion Our findings found that the effects of acupuncture at acupoints with lower versus higher PT were similar, both were effective for patients with KOA. Trial registration: ClinicalTrials.gov identifier: NCT03299439. Registered 3 October 2017, https://clinicaltrials.gov/ct2/show/NCT03299439